. Women’s precious role in the development of Africa in darko’s beyond the horizon, ngugi’s devil on the cross and a grain of wheat - HOUNDJO, THÉOPHILE; ALISSA, Vêssahou Gerson; AGBOADANNON, Koumagnon Alfred Djossou; GBEGNAVO, Nicholas (My University, 2022)
This paper aims at imparting to the reader the precious role that African women can play in the development process of their continent as dealt with in Darko’s on the Cross awareness is raised on how they can significantly impact their destiny by carving out a place for themselves in the society through daily struggles so as to emerge from the darkness from which tradition has sunk them for aeons o respective country and therefore Africa in general. The results of our findings will enable us to give more insights into country and Africa as a whole. With this in view, African women must awaken from their torpor so as to challenge the old image that people generally have of women in the world at large and in Africa in particular. Feminism, womanism and Marxist l in to the novels under study so as to reveal how both their form and content bear on the topic above by questioning the traditional image of women in Africa
Keywords: Women; Precious; Role; Development; Africa.